Exploring Value-oriented Storytelling Influences Traveler Loyalty Through Satisfaction and Image - Asraf Asraf; Nofal Supriaddin (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study explores the impact of Value-oriented Storytelling on Tourist Loyalty, with the mediation of Customer Satisfaction and Destination Image, using a sample of 196 tourists who visited the